Implementation of Food Hygiene and Sanitation Policy in the Kitchen of Class IIA Cibinong Prison Based on the Regulation of the Minister of Immigration and Corrections Number 1 of 2025 - Lily Pendiawaty; Ina Heliany (Sean Institute, 2025)
The importance of hygiene and sanitation in the kitchen of the Correctional Institution is to ensure that the food served to the inmates (WBP) is healthy, clean, and safe from contamination, thereby preventing the spread of disease. This includes the personal hygiene of officers and helpful WBPs, the use of Personal Protective Equipment (PPE) such as masks and gloves, and the cleanliness of the kitchen environment and equipment. In this study, the author specifically discusses the kitchen at the Cibinong Class IIA Correctional Institution. The formulation of the problems discussed is: 1) How is the implementation of food hygiene and sanitation policies in the kitchen of Class IIA Cibinong Prison? and 2) What factors affect the implementation of food hygiene and sanitation policies in the kitchen of Class IIA Cibinong Prison?. The research method used is the normative juridical method, namely research that prioritizes literature data, namely research on secondary data. The secondary data can be in the form of primary, secondary or tertiary legal materials. Based on the results of the research, the author concludes that the implementation of food hygiene and sanitation policies in the kitchen of the Class IIA Cibinong Prison is that the implementation of strict hygiene and sanitation practices at all stages of the food processing process—from the selection of raw materials, storage, processing, to presentation—is necessary to ensure safe, quality, nutritious, and healthy food for the Inmates, as well as to prevent disease and poisoning. The importance of Food Hygiene and Safety, because kitchen cleanliness is the main foundation in the processing of nutritious and clean food, ensuring the quality of health and taste of the food served to the Fostered Residents. The goal is to control factors such as raw materials, processes, people, and equipment to prevent contamination, bacterial breeding, as well as cross-contamination and recontamination that can cause diseases or health problems